"I Have a Cough": An Interactive Virtual Respiratory Case-Based Module - Nelia Afonso; Arati Kelekar; Anjali Alangaden (Association of American Medical Colleges, 2020)
Introduction The COVID-19 pandemic has radically disrupted traditional models of medical education, forcing rapid evolution in the delivery of clinical training. As a result, clinical educators must quickly transition away from in-person sessions and develop effective virtual learning opportunities instead. This virtual resource was designed to replace a clinical simulation session for the physical examination course for medical students in the preclinical years. Methods We designed an online interactive module in three sections for preclinical (first- or second-year) medical students who had not yet learned the respiratory physical exam. The first section incorporated demonstration and practice of the components of the respiratory physical exam that could be effectively taught via videoconferencing software. Following this, students conducted a telemedicine encounter with a standardized patient and received patient-centered feedback evaluating their communication skills. The final segment involved a case discussion and clinical reasoning component. Results These sessions were implemented for 122 first-year medical students. The module was well received by the students. A majority felt that it helped improve their telemedicine communication skills (93%), interpretation of physical exam findings (84%), development of differential diagnosis (95%), and correlation of clinical and basic science content (93%). Discussion Our pilot educational session demonstrates that this virtual instruction method is an effective tool for teaching basic clinical skills during medical school. Virtual learning resources allow remote instruction to take place and can be a supplement when face-to-face clinical teaching is not possible.